PENGARUH PERKAWINAN PULANG KABAKO TERHADAP KEUTUHAN KELUARGA DI DESA MUARA UWAI KEC.BANGKINANG KAB.KAMPAR - Sari, Devi Novita; Eddison, Ahmad; Zahirman, Zahirman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Humans are social beings, in the hold of a single human life requires more human.Humans live and thrive in the community interacting.By nature humans should be united, help each other, aligned and each pair.Humans have a tendency to form pairs of permanent or fixed by way of living together, these couples realized by an official relationship or bond called marriage.The background of this study the influence of the marital home kabako against the integrity of the family in the village of Muara Uwai kec.Bangkinang kab.Kampar.with the goal to be achieved in this research is to know is there any influence marital home kabako against the family unit.Samples taken in this study is 25 people.Engineering analysis using quantitative descriptive analysis using simple linear regression equation with the process through SPSS version 20.00.Based on the results of the study, marital return kabako no significant effect on the family unit in the village of Muara Uwai Kec.Bangkinang Kab.Kampar.based on the results of tests of significance were performed in this study with the results calculated F (1,04) ˂ F table (1.98).Simple linear regression equation obtained in this study is Y = 29 039 + 464X.this suggests that the marriage home kabako not affect the family unit in the village of Muara Uwai kec.Bangkinang kab.Kampar.Keywords: Marital Home Kabako, Wholeness Family